PENGARUH LINGKUNGAN PEMBELAJARAN JARAK JAUH TERHADAP PROKRASTINASI AKADEMIK - Salma Nava Pujiastuti; Dian Alfia Purwandari; Sujarwo Sujarwo (Jurnal Pendidikan, 2022)
This study aims to obtain an overview of the Influence of Distance Learning Environment on Academic Procrastination (Study on Students of Social Science Education, State University of Jakarta). The method in this study uses quantitative method with instruments in the form of questionnaires. Measuring instruments using likert scale. The population in this study was social science education students in the class of 2018-2020, with a sample of 155 respondents. Data retrieval techniques using probability sampling. Based on the results of the t-test analysis obtained 0.000 < 0.05 means there is an influence. Based on the results of linearity sig > 0.05 which means that between variables have a significant linear relationship. Based on the results of the coefficient of determination shows that the value of R Square of 0.191 this proves that, the variable environment of distance learning affects academic procrastination by 19.1% while the remaining 80.9% is the contribution of other variables that are not included in this study. So it can be concluded that the variables of distance learning environment affect academic procrastination in students of Social Science Education, State University of Jakarta.